History-dependent nucleation and growth of the martensitic phase in the magnetic shape memory alloy Ni45Co5Mn38Sn12 - Banerjee, A. (2014)
We study through the time evolution of magnetization the low-temperature (T) dynamics of the metastable coexisting phases created by traversing different paths in magnetic field H and T space in a shape memory alloy system, Ni45Co5Mn38Sn12. It is shown that these coexisting phases consisting of a fraction of kinetically arrested austenite phase and a remaining fraction of low-T equilibrium martensitic phase undergo a slow relaxation to low magnetization (martensitic) state but with very different thermomagnetic history-dependent rates at the same T and H. We discovered that, when the nucleation of the martensitic phase is initiated at much lower T through the de-arrest of the glasslike arrested state contrasted with the respective first-order transformation (through supercooling at much higher T), the long-time relaxation rate scales with the nonequilibrium phase fraction but has a very weak dependence on T. This is explained on the basis of the H-T path dependent size of the critical radii of the nuclei and the subsequent growth of the equilibrium phase through the motion of the interface.